A REVIEW OF WEED MANAGEMENT IN INDIA: THE NEED OF NEW DIRECTIONS FOR SUSTAINABLE AGRICULTURE - S. K. VERMA; S. B. SINGH; R. N. MEENA; S. K. PRASAD; R. S. MEENA; GAURAV (The Bioscan, 2015)
Weeds are the major deterrent to the development of sustainable crop production. Since weeds dictate most of the crop production practices and causes enormous losses (37 per cent) due to their interference. Farmers follow several practices for managing weeds in different crops/cropping systems, of which at present the use of herbicides are on the top due to the scarcity of labors. The sustainability of these systems is being questioned because of environmental, social, and economic concerns caused by global competition, production cost, soil erosion, environmental pollution, and concern over the quality of rural life. Enhancing the crop competitiveness through preventive methods, cultural practices, mechanical methods, plant breeding, biotechnology, biological control and crop diversification will be the central thesis in new paradigms of weed management. Integration of above techniques will be key to sustainable weed management that maintain or enhance the crop productivity, profitability and environmental quality. This article explores the scope of sustainable weed management, growing concerns over herbicide resistance, environmental and health hazards of pesticides including herbicides and declining profitability are the major challenges of ‘high input’ agriculture. The goal of this review is to facilitate the development of ecologically based alternative methods for sustainable weed management that will support crop production systems, which require less tillage, herbicide and other inputs. To accomplish this goal, research efforts must be radically expanded in crop ecology and in the development of ecologically based technologies for weed management. Adoption of sustainable agricultural practices reduces the intensity of soil manipulation thereby creates an unfavorable condition for weed seed germination, reduces the organic matter depletion and soil erosion. Thus, the sustainable approaches could be an option for weed and soil management which leads to sustainable crop production.